Secondary School Students and Internet Forums-A Survey of Student Views Contrasted with an Analysis of Internet Forum Posts - Johanna Dittmar; Ingo Eilks (MDPI AG, 2019)
Students today are increasingly engaged in the use of digital information and communication technologies. The Internet continues to grow and more and more young people are using it worldwide. Educational practices, however, have been slow to adapt to the corresponding developments. For example, Internet forums are generally ignored in most educational practices, including chemistry education, although they are often used to find new information by everyday people. The question therefore arises: Why are such media not used to provoke and promote science or chemistry teaching and learning, while simultaneously developing critical scientific media literacy? To understand how the younger generation learns via Internet forums, this article looks at a survey of Internet forum usage behavior by lower and upper secondary school students (age range 12−17) in relation to chemistry-specific content. The findings are then contrasted with an analysis of user behavior. The final analysis revealed that students are open and critical when using Internet forums, even though such learning is mostly unconnected to formal education. These results can inform science and chemistry teaching by focusing teaching and learning more on Internet forums in order to employ them as an educational medium in science class.